The Effect of Platinum-Based Chemotherapy in Advanced Non-Small Cell Carcinoma Lung Cancer (NSCLC) on Cardiovascular Events in Ulin Hospital Banjarmasin - Widya Ramadhaniati; Erna Kusumawardhani; Haryati Haryati; Dwi Laksono Adi Putro; Moh. Isa; Ali Assagaf (Jurnal Ners, 2025)
Chemotherapy for lung cancer can provide many benefits, but it also has side effects that cause side effects of treatment, one of which is in the field of cardiology. This study was conducted to assess the cardiovascular side effects of platinum-based chemotherapy in advanced stage non-small cell lung cancer. This research method uses a retrospective cohort design. Samples diagnosed with advanced stage KPKBSK who underwent first-line platinum-based chemotherapy underwent electrocardiography and echocardiography assessments at the beginning and after the fourth cycle or when cardiovascular disorders occurred to assess the incidence of atrial fibrillation, PAC, ST-T segment changes, prolonged QT, decreased EF and E/A ratio at Ulin Banjarmasin Regional General Hospital in April 2022-April 2023. The results of this study indicate that chemotherapy for lung cancer with hypertension has an effect on decreasing ejection fraction (p-value <0.05, OR: 0.409). In the group of lung cancer with coronary heart disease receiving chemotherapy, the incidence of atrial fibrillation increased (p-value <0.05, OR: 20). Furthermore, cardiovascular events such as atrial fibrillation increased (p-value <0.05, OR: 6.800) and PAC (p-value <0.05, OR: 6.800) in the squamous cell carcinoma and adenocarcinoma lung cancer groups (p-value <0.05, OR: 0.409). There was no decrease in the E/A ratio and prolonged QT with chemotherapy. The conclusion of this study is that there is no effect of platinum-based chemotherapy on cardiovascular events in advanced lung cancer, but administration to groups with comorbid hypertension and coronary heart disease has an effect on increasing cardiovascular events in lung cancer patients at Ulin Banjarmasin Hospital.